Current trends in peanut allergy immunotherapy: a review - Klementyna Łyżwa; Anna Krupa-Łaska; Joanna Zielińska; Marek Kulus; Katarzyna Grzela (Alergologia Polska)
Peanut allergy (PA) poses significant clinical challenges due to its potentially life-threatening nature and increasing prevalence, particularly in children. Strict avoidance is difficult due to the widespread presence of peanuts in various foods, leading to high rates of accidental exposure. Traditional management includes education, avoidance, and rescue medication. Recent advances in immunotherapy offer promising avenues for the management of PA. Various methods of immunotherapy have been investigated, including oral immunotherapy (OIT), sublingual immunotherapy (SLIT), and epicutaneous immunotherapy (EPIT). Immunotherapy is associated with challenges such as adverse effects, the risk of anaphylaxis, and the long-term persistence of tolerance. Combining immunotherapy with adjuvants such as omalizumab and dupilumab or probiotics is promising, but it raises questions about sustained efficacy and patient response after treatment discontinuation. In addition, the translation of clinical trial results into real-world settings remains a critical issue, as shown by low participation rates in immunotherapy programs. Immunotherapy for peanut allergy has the potential to be a game-changer in the treatment of peanut allergies. However, it is important to note that this treatment is not without its challenges. Further research, collaboration between clinicians and researchers, and addressing patient concerns are needed to establish immunotherapy as a safe and effective treatment option for individuals with peanut allergy.